Knowledge, attitudes, and practices among the general community population toward heatstroke - Xu, Yangfeng; Chen, Jianping; Du, Jinkang; Jin, YunYing (Frontiers in Public Health, 2024)
Background and objective Heatstroke (HS) is a life-threatening condition resulting from thermal injury within the body, and it is associated with a significantly high mortality rate. This study aimed to assess the knowledge, attitudes and practices (KAP) among the general community population toward heatstroke. Methods The web-based cross-sectional study was conducted between September 2023 and October 2023 at the Emergency Department of Dongyang People's Hospital. A self-designed questionnaire was developed to collect demographic information of the general community population and to assess their knowledge, attitudes and practices toward heatstroke. Results A total of 1,356 valid questionnaires were collected. Among the participants, 875 (64.53%) were female, and 496 (36.58%) had regular exercise. The mean knowledge, attitudes and practices scores were 12.73 ± 1.42 (possible range: 0–14), 33.74 ± 2.91 (possible range: 8–40) and 34.65 ± 5.30 (possible range: 8–40), respectively. The structural equation model demonstrated that education had direct effects on knowledge (β = 0.017, p < 0.001), attitudes (β = 0.123, p < 0.001), and practices (β = −0.094, p < 0.001). Moreover, knowledge had direct effects on attitudes (β = 1.920, p < 0.001), and attitudes had direct effects on practices (β = 0.642, p < 0.001). Conclusion The findings revealed that the general community population have sufficient knowledge, active attitudes and proactive practices toward the heatstroke. However, there is still room for improvement and it is necessary to develop and implement educational initiatives and interventions designed to further enhance their KAP toward heatstroke.